The mysterious provenance and uncommon repertoire of the music collection belonging to the Dominican Pius Hancke - Hauptman-Fischer, Ewa (Interdisciplinary Studies in Musicology, 2018)
Father Pius Hancke’s music collection includes numerous pieces written for harp. Its outstanding repertoire and provenance distinguishes it from other monastic collections. Hancke expanded it throughout his life and took it with him when moving home. He spent the last thirty years of his life in the Dominican monastery in Nysa. Music for the liturgy contained in his collection (masses, litanies) was certainly used there and is currently the only testimony of that monastery’s musical culture. Besides liturgical compositions, Hancke’s collection includes a number of instrumental pieces for harp with the accompaniment of other instruments and contrafacta of operatic arias. The latter often include parts arranged for harp, probably by Hancke himself. The scriptors’ names link this collection to a unique manuscript containing a Credo ascribed to Antonio Vivaldi.